The past, present and future of educational assessment: A transdisciplinary perspective - Brown, Gavin T. L. (Frontiers in Education, 2022)
To see the horizon of educational assessment, a history of how assessment has been used and analysed from the earliest records, through the 20th century, and into contemporary times is deployed. Since paper-and-pencil assessments validity and integrity of candidate achievement has mattered. Assessments have relied on expert judgment. With the massification of education, formal group-administered testing was implemented for qualifications and selection. Statistical methods for scoring tests (classical test theory and item response theory) were developed. With personal computing, tests are delivered on-screen and through the web with adaptive scoring based on student performance. Tests give an ever-increasing verisimilitude of real-world processes, and analysts are creating understanding of the processes test-takers use. Unfortunately testing has neglected the complicating psychological, cultural, and contextual factors related to test-taker psychology. Computer testing neglects school curriculum and classroom contexts, where most education takes place and where insights are needed by both teachers and learners. Unfortunately, the complex and dynamic processes of classrooms are extremely difficult to model mathematically and so remain largely outside the algorithms of psychometrics. This means that technology, data, and psychometrics have become increasingly isolated from curriculum, classrooms, teaching, and the psychology of instruction and learning. While there may be some integration of these disciplines within computer-based testing, this is still a long step from where classroom assessment happens. For a long time, educational, social, and cultural psychology related to learning and instruction have been neglected in testing. We are now on the cusp of significant and substantial development in educational assessment as greater emphasis on the psychology of assessment is brought into the world of testing. Herein lies the future for our field: integration of psychological theory and research with statistics and technology to understand processes that work for learning, identify how well students have learned, and what further teaching and learning is needed. The future requires greater efforts by psychometricians, testers, data analysts, and technologists to develop solutions that work in the pressure of living classrooms and that support valid and reliable assessment.